A review of penicillin binding protein and group A Streptococcus with reduced-β-lactam susceptibility - Yu, Dingle; Guo, Danchun; Zheng, Yuejie; Yang, Yonghong (Frontiers in Cellular and Infection Microbiology, 2023)
With the widespread use of antibiotics, antimicrobial resistance (AMR) has become a global problem that endangers public health. Despite the global high prevalence of group A Streptococcus (GAS) infections and the global widespread use of β-lactams, β-lactams remain the first-line treatment option for GAS infection. β-hemolytic streptococci maintain a persistent susceptibility to β-lactams, which is an extremely special phenomenon in the genus Streptococci, while the exact current mechanism is not known. In recent years, several studies have found that the gene encoding penicillin binding protein 2X (pbp2x) is associated with GAS with reduced-β-lactam susceptibility. The purpose of this review is to summarize the current published data on GAS penicillin binding proteins and β-lactam susceptibility, to explore the relationship between them, and to be alert to the emergence of GAS with reduced susceptibility to β-lactams.